MENGENAL MARGA LUTJANUS, SALAH SATU KOMODITAS UNGGULAN DALAM PERIKANAN TANGKAP - Selvia Oktaviyani (OSEANA, 2018)
NOTES ABOUT LUTJANUS, ONE OF MAIN COMMODITIES IN CAPTURE FISHERIES. The snapper, genus Lutjanus are commercially important fish species, distributed in tropical to temperate regions all over the world. This group is mostly reef associated marine fishes and several deep-water (>100 m) species. Genus Lutjanus contains the largest number of species, i.e. 72 species in the world and almost 33 species in Indonesian waters. The snappers are dioecious and gonochoristic organisms, this means that they have separate sexes and the sexual differentiation remains constant throughout their life span. They are carnivorous and the diet consist mainly of small fishes, crustaceans, mollucas, and pelagic urochordata.